2020
DOI: 10.14245/ns.1938420.210
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Chemoprophylaxis Within 24 Hours of Surgery for Spinal Cord Injury: Is It Safe and Effective?

Abstract: Objective: Current guidelines recommend initiation of venous thromboembolism (VTE) chemoprophylaxis within 72 hours of spinal cord injury (SCI). This study investigated the safety and efficacy of chemoprophylaxis within 24 hours of surgery for SCI. Methods: A retrospective review of 97 consecutive patients who underwent surgery for acute traumatic SCI at a single level 1 trauma center from 2013-2018 was performed. VTE/ postoperative bleeding rates during hospitalization, demographics, medical/surgical complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Comprehensive evaluation of the 17 selected manuscripts was conducted. Finally, five articles were found to meet the inclusion criteria of this meta-analysis [ 16 20 ]. The details of the included cohort studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comprehensive evaluation of the 17 selected manuscripts was conducted. Finally, five articles were found to meet the inclusion criteria of this meta-analysis [ 16 20 ]. The details of the included cohort studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies compared the effects of LMWH and UFH in preventing VTE in patients with SCI [ 16 , 18 20 ]. The incidence of VTE in the LMWH treatment group was 10.3–53.4%, and the incidence of VTE in the UFH treatment group was 4.0–77.6%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, determining the optimal timing of initiation of chemoprophylaxis following SCI or spinal fracture is of paramount importance, but is also somewhat controversial. While the overall strength of scientific evidence is low, it appears that initiation of pharmacologic VTE prophylaxis within 48 hours of injury or spine surgery is associated with a reduced incidence of DVT and PE, with no associated increase in hemorrhagic complications 55–57 …”
Section: Protocol Rationale and Goalsmentioning
confidence: 99%
“…Studies have reported that if DVT is not treated in time, it can lead to patients with large-scale pulmonary embolism and the incidence rate is 20 %-30 % [7] . DVT treatment includes a lot of joint contents such as thrombolytic therapy, anticoagulation, Inferior Vena Cava (IVC) filter indwelling, mechanical thrombectomy, Traditional Chinese Medicine (TCM), acupoint compression and psychological intervention [8,9] .…”
mentioning
confidence: 99%